2019
DOI: 10.3390/s19092123
|View full text |Cite
|
Sign up to set email alerts
|

Gas Sensors Based on Mechanically Exfoliated MoS2 Nanosheets for Room-Temperature NO2 Detection

Abstract: The unique properties of MoS2 nanosheets make them a promising candidate for high-performance room temperature gas detection. Herein, few-layer MoS2 nanosheets (FLMN) prepared via mechanical exfoliation are coated on a substrate with interdigital electrodes for room-temperature NO2 detection. Interestingly, compared with other NO2 gas sensors based on MoS2, FLMN gas sensors exhibit high responsivity for room-temperature NO2 detection, and NO2 is easily desorbed from the sensor surface with an ultrafast recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 67 publications
1
41
0
1
Order By: Relevance
“…17,37 However, some other works indicated that in spite of slow rates of gas adsorption and desorption, the pristine MoS 2 -based sensors showed the complete recovery at RT to target gases. 20,[38][39][40] This characteristic can be attributed to several factors, such as high specic surface area, defective/strained surface and weak van der Waals binding between the target gas and the MoS 2 surface. 20,38,39 In addition, Ikram et al indicated that the high specic surface area not only increases the response of the sensor but also plays an important role in fast response and recovery times.…”
Section: Resultsmentioning
confidence: 99%
“…17,37 However, some other works indicated that in spite of slow rates of gas adsorption and desorption, the pristine MoS 2 -based sensors showed the complete recovery at RT to target gases. 20,[38][39][40] This characteristic can be attributed to several factors, such as high specic surface area, defective/strained surface and weak van der Waals binding between the target gas and the MoS 2 surface. 20,38,39 In addition, Ikram et al indicated that the high specic surface area not only increases the response of the sensor but also plays an important role in fast response and recovery times.…”
Section: Resultsmentioning
confidence: 99%
“… Pt/Ti Resistor 0.5 200 11 33 107 [ 24 ] MoS 2 Nanosheets p M.E. Ag/Pd Resistor 100 RT 29 42 2 [ 309 ] MoS 2 -W n Hyd. Ag/Pd Resistor 20 RT 171 41 39 [ 121 ] MoS 2 -Au p S.P.…”
Section: Experimental Investigations Of No 2 Adsormentioning
confidence: 99%
“…Similarly (Figure 9b), DFT calculations indicated that the fairly fast recovery of MoS2 arises from the weak van der Waals interactions between NO2 and the MoS2 surface. Furthermore, exfoliated few-layer MoS 2 nanosheets deposited on a substrate with interdigitated electrodes demonstrated good NO 2 detection performances at room temperature [168]. The reported device shows a quick and complete recovery time of 2 s at a rate greater than 97%.…”
mentioning
confidence: 90%
“…Due to the strong response and excellent signal-to-noise ratio, a detection limit of TEA as low as 10 ppb was achieved. Furthermore, exfoliated few-layer MoS2 nanosheets deposited on a substrate with interdigitated electrodes demonstrated good NO2 detection performances at room temperature [168]. The reported device shows a quick and complete recovery time of 2s at a rate greater than 97%.…”
mentioning
confidence: 91%